Uji Aktivitas Antimalaria Ekstrak Kering DaunTithonia diversifolia pada Mencit yang Diinfeksi Plasmodium berghei (Antimalarial Activity of Dry Extract of Tithonia diversifolia Leaves on Plasmodium berghei Infected Mice) - Novan Eko Setiyanggono; Nuri .; Endah Puspitasari (Pustaka Kesehatan, 2014)
Malaria is an infectious disease caused by Plasmodium sp. One of the herbs that are empirically used as an antimalarial is Tithonia diversifolia. Preparation of dried leaf extract of T. diversifolia used oven drying and the addition of cab-o-sil as a dryer. This study aims to determine the antimalarial activity of extracts of dried leaves of T. diversifolia. Antimalarial activity assay method used was a modified peter test. The probit analysis of this study showed that ED50 value on mice given the dry extract of T. diversifolia leaves was 214 mg /kg body weight and categorized as good at classifying antiplasmodium in vivo.     Keywords: antimalarial activity, Tithonia diversifolia, dry extract, ED50